Graying with dignity: Negotiating public service delivery amidst gaps in the welfare of rural Trenggalek's aging population - Setijaningrum, Erna; Samad, Suhaimi; Triana, Rochyati Wahyuni (Masyarakat, Kebudayaan dan Politik, 2023)
As global demographics gravitate toward aging populations, developing nations, Indonesia included, face the demanding obligation of providing adequate healthcare and social services for their elderly demographic, particularly in rural areas. This paper delves into the complexities of elderly care in Trenggalek Regency, situated in East Java, Indonesia, where it centers on describing the firsthand experiences of the elderly residents and their challenges in accessing healthcare, maintaining financial stability, and navigating the adequacy of infrastructure. Insights revealed the notions of elderly public service, pointing out both progress and challenges in affordable care, with many seniors relying on limited family support and resorting to informal work to sustain themselves, while mobility issues, including transportation deficits and challenging terrain, deepen their social isolation. However, it also spotlights ongoing local policy endeavors, crafted to address these challenges, acknowledging the pressing need for change and striving to elevate the quality of elderly care services. In doing so, the paper offers practical insights into elderly care disparities in developing country contexts and emphasizes the vital role played by rural elderly communities in shaping proper interventions, valuing their insights and experiences in sculpting the future of geriatric care in Trenggalek and beyond.